Caribbean energy sector : review and perspectives. Part I - Primary energy. Part II - Electricity. - BOOPSINGH, Trevor M. (1994)
Points out that petroleum and petroleum derived products would remain the dominant energy source in the next century, with electricity being the other critical energy requirement. Presents some perspectives on the global technology trends in the provision of these two critical commodities, if practical, viable and realistic proposals for satisfying the energy needs of the Caribbean are to be met.